Three-dimensional in vivo kinematics and finite helical axis variables of the ovine stifle joint following partial anterior cruciate ligament transection. (9th May 2019) - Barton, Kristen I.; Shekarforoush, Mehdi; Heard, Bryan J.; Sevick, Johnathan L.; Martin, C. Ryan; Frank, Cyril B.; Hart, David A.; Shrive, Nigel G.
Abstract: Partial anterior cruciate ligament (p-ACL) rupture is a common injury, but the impact of a p-ACL injury on in vivo joint kinematics has yet to be determined in an animal model. The in vivo kinematics of the ovine stifle joint were assessed during 'normal' gait, and at 20 and 40 weeks after p-ACL transection (Tx). Gross morphological scoring of the knee was conducted. p-ACL Tx creates significant progressive post-traumatic osteoarthritis (PTOA)-like damage by 40 weeks. Statistically significant increases for flexion angles at hoof-strike (HS) and mid-stance (MST) were seen at 20 weeks post p-ACL Tx and the HS and hoof-off (HO) points at 40 weeks post p-ACL-Tx, therefore increased flexion angles occurred during stance phase. Statistically significant increases in posterior tibial shift at the mid-flexion (MF) and mid-extension (ME) points were seen during the swing phase of the gait cycle at 40 weeks post p-ACL Tx. Correlation analysis showed a strong and significant correlation between kinematic changes (instabilities) and gross morphological score in the inferior-superior direction at 40 weeks post p-ACL Tx at MST, HO, and MF. Further, there was a significant correlation between change in gross morphological combined score (ΔGCS) and the change in location of the helical axis in the anterior direction (ΔsAP) after p-ACL Tx for all points analyzed through the gait cycle. This study quantified in vivo joint kinematics before and after p-ACL Tx knee injury during gait, and demonstrated that a p-ACL knee injury leads to both PTOA-like damage and kinematic changes.